Immunosuppressive therapy to reduce mitral regurgitation in Libman–Sacks endocarditis: a case report - Ishizu, Kenichi (Eur Heart J Case Rep, 2019)
BACKGROUND: Libman–Sacks endocarditis is a cardiac manifestation of systemic lupus erythematosus (SLE) and is characterized by non-bacterial verrucous vegetations, causing valvular stenosis and/or regurgitation. The effectiveness of immunosuppressive therapy for valve dysfunction due to Libman–Sacks endocarditis has not been reported. CASE SUMMARY: A 67-year-old woman with a history of chronic atrial fibrillation was emergently admitted with acute decompensated heart failure. Transoesophageal echocardiogram revealed severe mitral regurgitation (MR) due to oedematous thickening and poor coaptation of the medial edge of A2/P2 segments and the lateral edge of A3/P3 segments. Serial blood culture results were negative, suggesting bacterial infective endocarditis to be a less likely cause of valvular damage. Because the patient developed photosensitivity, livedo reticularis, and pancytopenia, Libman–Sacks endocarditis with rapidly progressive SLE was diagnosed on the basis of positive test results of anti-double-stranded DNA-IgG and its complement titer. Two months after, immunosuppressive therapy including corticosteroids, a transoesophageal echocardiogram revealed thinning of the degenerative mitral valve leaflets and a reduction of MR from severe to mild. DISCUSSION: Corticosteroid therapy for Libman–Sacks endocarditis reportedly increases the extent of fibrosis and scarring of the valve leaflets, resulting in worse valve function. In our patient, MR decreased from severe to mild after corticosteroid therapy. Because low-echoic thickening of the mitral valve leaflets suggested acute oedematous changes without scarring and fibrosis and other clinical symptoms of SLE rapidly progressed, early initiation of immunosuppressive therapy for Libman–Sacks endocarditis lead to a benign clinical course in our patient.